Design and Experimental Research on Staggered Straw Cleaning Device for No-Till Seeding in Drip Irrigation Area - Panpan Yuan; Xingliang Zhu; Xuejun Zhang; Jia You; Jinshan Yan; Shilong Qiu (Agronomy)
To solve the problem of straw cleaning and drip irrigation belt restoration for no-till seeding in drip irrigation areas, a staggered straw cleaning device was developed for no-till seeding, which is mainly composed of a front two-sided tine discs group, a drip irrigation belt laying mechanism, a middle single inner tine discs group, a rear single outer tine discs group. Different tine disc groups are set in longitudinal, transverse, and radial directions to move and throw the straw on the surface of the seeding strip. The critical parameters of the tine disc were designed and calculated, and the radius was determined to be 160 mm, the number of teeth was 12, and the theoretical working width was obtained. The movement and straw scattering process were analyzed, and the main influencing factors and the maximum straw scattering distances in the horizontal and vertical directions were determined. The interaction model of staggered tine discs group–straw–soil is established using the discrete element method (DEM). The forwarding speed, rotating speed, disc rake angle, and lateral distance of the middle tine discs were used as influencing factors, and the straw cleaning rate and the mass of straw returned in the drip irrigation coverage area were selected as the text indexes to carry out quadratic orthogonal rotation experiments. The quadratic regression model of the three sensitive parameters on the cleaning rate and the mass of straw returned in the drip irrigation coverage area was constructed and optimized. The optimal solutions were obtained: the forwarding speed was 9 km/h, the disc rake angle was 33.7°, and the lateral distance of the middle tine discs was 529 mm. The field validation test was carried out, and the results showed that the straw cleaning was 89.13%, the straw cleaning width of the seed strip was 527.2 mm, and the straw coverage rate of the drip irrigation area was 80.74%. This achievement can provide a reference for straw cleaning of no-till seeding under drip irrigation.